2007
DOI: 10.1080/13880200701538666
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Salidroside on Hypoxia/Reoxygenation Injury by Sodium Hydrosulfite in PC12 Cells

Abstract: Hypoxia=reoxygenation causes cellular injury and death associated with many pathophysiologic conditions, including respiratory disorders, myocardial ischemia, and tumour progression diseases. Neuronal pheochromocytoma (PC12) cells are widely used as a model system for neurologic research and are subject to chemical hypoxia induced with sodium hydrosulfite (Na 2 S 2 O 4 ), a common oxygen-consuming agent. Salidroside, which is the main active component of the famous traditional Chinese herb Rhodiola rosea L. (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with the published data on epigalokhin, a polymeric proanthocyanidin isolated from a related species, R. semenovii, which exhibited pronounced antihypoxic effect in both in-vivo and in-vitro experiments [21]. Additionally, the most abundant phenylethanoid glycoside, salidroside, was reported to exert a protective effect on PC12 (neuronal pheochromocytoma cells), where it prevented the morphological changes of these cells under conditions of chemical hypoxia induced by Na 2 S 2 O 4 [22] . R. heterodonta rhizome contains a wide range of secondary metabolites including polymeric proanthocyanidins [15], which interfere with direct HPLC analysis.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are consistent with the published data on epigalokhin, a polymeric proanthocyanidin isolated from a related species, R. semenovii, which exhibited pronounced antihypoxic effect in both in-vivo and in-vitro experiments [21]. Additionally, the most abundant phenylethanoid glycoside, salidroside, was reported to exert a protective effect on PC12 (neuronal pheochromocytoma cells), where it prevented the morphological changes of these cells under conditions of chemical hypoxia induced by Na 2 S 2 O 4 [22] . R. heterodonta rhizome contains a wide range of secondary metabolites including polymeric proanthocyanidins [15], which interfere with direct HPLC analysis.…”
supporting
confidence: 90%
“…In one study it was reported that the concentrations of salidroside and tyrosol ranged from 1.3-11.1 mg/g and 0.3- 2.2 mg/g, respectively in dry Rhodiola rosea rhizomes collected from various parts of China [22]. In another study, the concentration of salidroside in a selection of dried R. rosea samples ranged from 0.4 to 2.7 mg/g [23].…”
mentioning
confidence: 99%
“…Salidroside, an active component of the medicinal plant Rhodiola rosea , has anticancer, antiapoptotic, and anti-inflammatory effects, along with hepatorenal and cardiovascular protective functions [10]. Its antitumor effect is related to cell cycle arrest at G1 phase via regulation of the cyclin-dependent kinase (CDK) 4-cyclin protein D1 pathway or at the G2 phase via the CDK2-cyclin B1 pathway [11].…”
Section: Introductionmentioning
confidence: 99%